PENERAPAN KARAKTER PENDIDIK DALAM PEMBELAJARAN: KAJIAN QS. AL-FUSHSHILAT AYAT 34-35 DALAM TAFSIR AL-MISBAH - Eka Wahyu Hidayati; Cicik Nafisatur Rizqiyah (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
This study used content analysis. The character of the educator in the perspective of the Qur'an Surah Fushshilat verses 34-35 In the first verse, namely verse 34, Allah (swt) explained to the Holy Prophet Muhammad that good and bad are not the same. Then Allah (swt) commanded the Prophet to fight against evil with better deeds instead of similar ugliness and in dealing with one's foolishness meekly, forgiving mistakes and dealing with anger patiently. Verse 35 is not all capable of resisting the evil that befalls him with a good except those who are endowed with Allah, personality, patience in their souls, and great fortune in the world and in the end. Useful, useful values, always upheld and as a reference for behavior for human life. While morality is a trait embedded in the soul, which is in the form of desires that encourage a person to do a good or bad deed, continuously or continuously, without requiring deep thought and consideration